Cyclic loading tests of earthquake-resilient prefabricated steel cross joints with different FCP connections. (August 2021) - Zhang, Ai-lin; Su, Lei; Jiang, Zi-qin; Kang, Yi-tao; Qiu, Ping
Abstract: Prefabricated steel structure has been promoted in construction for its advantages in the greening, industrialization and informatization of buildings. Meanwhile, the earthquake-resilience of steel structures has become a research hotspot in the field of international seismic engineering. In this paper, five earthquake-resilient prefabricated steel beam-column cross joints (ERPCJs) were studied by the low-cyclic loading tests. The influence of flange connecting bolts number, flange connection forms, bolt distance of middle row and bolt hole forms on the seismic performance, failure mode and other key performance indexes were studied. The tests results show that ERPCJs with reasonable parameters have outstanding bearing capability and seismic behavior. The beams of each specimen were damaged slightly or basically free from damage. Also, earthquake-resilient requirement could be quickly achieved by replacing connecting plates and high-strength bolt groups. Reducing the connecting bolts could make the joint fully utilize the sliding friction of flange cover plates (FCPs) to dissipate energy, and enhance ductility and rotation of the joint, but it could reduce joint's initial stiffness and ultimate bearing capability at the same time. The smaller bolt distance of middle row has little effect on the yielding load of the joint, but can improve joint's ultimate bearing capability. Besides, slotted holes on the cantilever beam can avoid the stressconcentration resulting from the compression of bolt rods and bolt hole walls, as well as can also effectively realize sliding energy dissipation of the FCPs.